PENGARUH KETERIKATAN KARYAWAN (EMPLOYEE ENGAGEMENT) TERHADAP KINERJA KARYAWAN DI PT. BADJA BARU PALEMBANG - yudi muliawan; badia perizade; afriyadi cahyadi (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2017)
This study aimed to find out the influence of employee engagement on theemployee performance. The independent variable was Employee Engagement (X) andthe dependent variable was Performance (Y). The data collection technique used asaturated sampling or census. The questionnaire was distributed to all employees ofPT.BadjaBaru Palembang. The data were analyzed using Simple Regression Analysis.The result of the study shows that the employee engagement has a positive andsignificant influence on the employee performance.Keywords: Employee Engagement, Performance